2022
DOI: 10.1136/bmjresp-2021-001186
|View full text |Cite
|
Sign up to set email alerts
|

Association of respiratory symptoms with body mass index and occupational exposure comparing sexes and subjects with and without asthma: follow-up of a Norwegian population study (the Telemark study)

Abstract: BackgroundOccupational exposure and increased body mass index (BMI) are associated with respiratory symptoms. This study investigated whether the association of a respiratory burden score with changes in BMI as well as changes in occupational exposure to vapours, gas, dust and fumes (VGDF) varied in subjects with and without asthma and in both sexes over a 5-year period.MethodsIn a 5-year follow-up of a population-based study, 6350 subjects completed a postal questionnaire in 2013 and 2018. A respiratory burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…This study also indicated that teachers with an overweight BMI (>18.5 kg/m 2 ) were 2.57 times more likely to develop chronic respiratory symptoms than teachers with a normal BMI (18.5–24.9 kg/m 2 ). Other plausible investigations correspondingly confirm that an increase in weight (overweight) is associated with respiratory health problems 65–67. The potential explanation for our finding is that being overweight affects the respiratory system by several mechanisms: direct mechanical changes due to fat deposition on the chest wall, blood vessels, abdomen and upper airway as well as systemic inflammation 68 69.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study also indicated that teachers with an overweight BMI (>18.5 kg/m 2 ) were 2.57 times more likely to develop chronic respiratory symptoms than teachers with a normal BMI (18.5–24.9 kg/m 2 ). Other plausible investigations correspondingly confirm that an increase in weight (overweight) is associated with respiratory health problems 65–67. The potential explanation for our finding is that being overweight affects the respiratory system by several mechanisms: direct mechanical changes due to fat deposition on the chest wall, blood vessels, abdomen and upper airway as well as systemic inflammation 68 69.…”
Section: Discussionsupporting
confidence: 81%
“…Other plausible investigations correspondingly confirm that an increase in weight (overweight) is associated with respiratory health problems. 65–67 The potential explanation for our finding is that being overweight affects the respiratory system by several mechanisms: direct mechanical changes due to fat deposition on the chest wall, blood vessels, abdomen and upper airway as well as systemic inflammation. 68 69 Being overweight causes fat accumulation in the body, which changes respiratory physiology and results in the impairment of various lung function parameters.…”
Section: Discussionmentioning
confidence: 86%
“…Our results showing that men working outside have clear risk for IPD may indicate that if the airways are exposed to harsh conditions, the sensitivity for different contact dimensions increases. The underlying assumption is that men are more exposed to fumes, dust, and irritants, which has been observed in both industrial cohorts and in general‐population‐based studies 27−28 . Another possible reason why men have an increased risk is that there are physiological differences between the genders, which affect both hormonal activities and the and immune system 29 …”
Section: Discussionmentioning
confidence: 99%
“…The underlying assumption is that men are more exposed to fumes, dust, and irritants, which has been observed in both industrial cohorts and in general‐population‐based studies. 27 , 28 Another possible reason why men have an increased risk is that there are physiological differences between the genders, which affect both hormonal activities and the and immune system. 29 …”
Section: Discussionmentioning
confidence: 99%